We all have problems ... Ethnographic museums and development in “Western” Europe (Cadernos de Sociomuseologia, 2014)
In the first part, I will explore changes in society in recent years that somehow are connected to the idea of development, largely based on the literature review. I will help mainly on the argumentation and Jan Nederveen Pieterse perspective (1997) with regard to multiculturalism. Will also try to reflect on the contributions of our discussion group, referring only a few examples. In the second part, I will discuss these topics in the light of development ideas, first giving some explanation about development as a concept and then combining it with the proposals for museums in Europe "Western" countries with regard to social inclusion and intercultural communication.Keywords: Hybridity; participation; development; community; museologyNa primeira parte, explorarei transformações da sociedade nos últimos anos que, de alguma forma, se encontram ligadas à ideia de desenvolvimento, em grande parte baseadas na revisão da literatura. Socorrer-me-ei principalmente da argumentação e da perspectiva de Jan Nederveen Pieterse (1997) no que se refere ao multiculturalismo. Também tentarei reflectir no contributo do nosso grupo de discussão, referindo apenas alguns exemplos. Na segunda parte, discutirei estes tópicos à luz das ideias de desenvolvimento, primeiro dando alguma explicação sobre desenvolvimento enquanto conceito e depois combinando-o com as propostas para museus em países europeus “ocidentais” no que respeita a inclusão social e comunicação intercultural.Palavras-chave: Hibridismo; participação; desenvolvimento; comunidade; museologia